Juvenile polyposis syndrome - Tasadooq Hussain; James M. Church (Clinical Case Reports, 2020)
Abstract Juvenile polyposis syndrome (JPS) patients can have a significantly high burden of polyposis. Patient who undergoes prophylactic colectomy for polyps not amenable to endoscopic treatments requires close clinical surveillance to negate risk of malignancy from interval polyposis.